Sensitivity of typhoon modeling to surface waves and rainfall. Issue 3 (4th March 2017) - Zhao, Biao; Qiao, Fangli; Cavaleri, Luigi; Wang, Guansuo; Bertotti, Luciana; Liu, Li
Abstract: Improving intensity simulation and forecast of tropical cyclones has always been a challenge, although in recent years the track forecasts have been remarkably improved. In this study, we explore the sensitivity of typhoon simulation to three physical processes using a fully coupled atmosphere‐ocean‐wave model. Two storms, a strong and a weak one, have been chosen. The effects of wave breaking induced sea spray, ocean vertical mixing associated with nonbreaking surface waves, and sea surface cooling due to intense rainfall are assessed by means of a set of numerical experiments. The results show and confirm that sea spray leads to an increase of typhoon intensity by enhancing the air‐sea heat flux, while nonbreaking wave‐induced vertical mixing and rainfall lead to a decrease. Each process can be relevant, depending on wind and wave conditions. These can vary dramatically when typhoons interact with not sufficiently well‐defined coastal areas, typically an archipelago. Compared with the control runs, when all the three physical processes are considered, the (absolute) difference between the modeled sea level pressure and best track data is reduced from 26.05 to 0.70 hPa for typhoon Haiyan, and from −9.42 to −8.67 hPa for typhoon Jebi. We have found a steady overestimate of the dimensions of the typhoons. We have verified an extreme sensitivity to the initial conditions, especially when small differences in the typhoon track may imply different relevance of the physical processes, like the ones we have considered, governing the evolution of the storm. Plain Language Summary: Improving intensity forecast of tropical cyclones has always been a challenge during the past decades. In this study, we explore the sensitivity of typhoon simulation to three physical physical processes using a fully coupled atmosphere‐ocean‐wave model: The effects of wave breaking induced sea spray, ocean vertical mixing associated with nonbreaking surface waves, and sea surface cooling due to intense rainfall are assessed by means of a set of numerical experiments. The results show and confirm that sea spray leads to an increase of typhoon intensity by enhancing the air‐sea heat flux, while nonbreaking wave‐induced vertical mixing and rainfall lead to a decrease. Compared with the control runs, when all the three physical processes are considered, the (absolute) difference between the modeled sea level pressure and best track data is reduced from 26.05 to 0.70 hPa for typhoon Haiyan, and from −9.42 to −8.67 hPa for typhoon Jebi, with the former a very strong Typhoon and the latter a quite weak one. These understandings are helpful for improving intensity simulation and forecast. Key Points: Three physical processes of sea spray, nonbreaking wave‐induced vertical mixing, and rainfall are considered in a fully atmosphere‐ocean‐wave coupled typhoon model Sea spray leads to an increase in typhoon intensity, while nonbreaking wave‐induced vertical mixing and rainfall lead to a decrease Typhoon tracks are sensitive to initial conditions